To be where you are eaudiobook - Karon, Jan (Mitford, 2017)
A  NEW YORK TIMES  BESTSELLER #1  New York Times -bestselling author Jan Karon returns with the fourteenth novel in the beloved Mitford series, featuring three generations of Kavanaghs. Wounds heal, bonds grow stronger, and celebrations continue...Welcome back to beloved Mitford.  After twelve years of wrestling with the conflicts of retirement, Father Tim Kavanagh realizes he doesn't need a steady job to prove himself. Then he's given one. As for what it proves, heaven only knows. Millions of Karon fans will be thrilled that it's life as usual in the wildly popular Mitford series: A beloved town character lands a front-page obituary, but who was it, exactly, who died? And what about the former mayor, born the year Lindbergh landed in Paris, who's still running for office? All this, of course, is but a feather on the wind compared to Muse editor J.C. Hogan's desperate attempts to find a cure for his marital woes. Will it be high-def TV or his pork-chop marinade? In fiction, as in real life, there are no guarantees.  Twenty minutes from Mitford at Meadowgate Farm, newlyweds Dooley and Lace Kavanagh face a crisis that devastates their bank account and impacts their family vet practice. But there is still a lot to celebrate, as their adopted son, Jack, looks forward to the most important day of his life—with great cooking, country music, and lots of people who love him. Happily, it will also be a day when the terrible wound in Dooley's biological family begins to heal because of a game—let's just call it a miracle—that breaks all the rules. In  To Be Where You Are , Jan Karon weaves together the richly comic and compelling lives of two Kavanagh families, and a cast of characters that readers around the world now love like kin.